Epidemiological analysis of foodborne diseases in China from 2011 to 2020 - CHEN Ting; ZHOU Qingqiong; QI Ping; LIN Zihao; MAO Xinwu (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveTo provide a basis for preventive initiatives against foodborne diseases， the trends of foodborne diseases in China from 2011 to 2020 were analyzed.MethodsDescriptive epidemiological analysis was conducted using data on foodborne diseases in China from 2011 to 2020.ResultsA total of 34 588 outbreaks occurred from 2011 to 2020， resulting in 259 481 illnesses， with 60.82% of incidents occurring from June to September. Plant and animal toxicants caused 43.56% of the outbreaks， followed by unknown etiology （35.49%） and bacteria and viruses （16.42%）. Fungi and their products accounted for the highest proportion of events （18.33%） and deaths （52.69%）. Restaurants （49.31%） and households （46.68%） were the most exposed. The average annual growth rate of household outbreaks was the highest （33.66%）.ConclusionPlant and animal toxicants， especially fungi and their products， were the main pathogenic factor of foodborne outbreaks in China in the last 10 years. Epidemic peaks of foodborne pathogens were observed in June and September. The exposure area was dominated by catering service units and households， with a tendency towards households.